"FALLEN ANGEL" OR VICTIM OF SOCIETY? DUALISTIC PORTRAYALS OF FEMININITY IN THOMAS HARDY'S "TESS OF THE D'URBERVILLES"- A CRITICAL STUDY (Contemporary Journal of Social Science Review, 2025)
Thomas Hardy’s Tess of the D’Urbervilles presents one of the most compelling and complex representations of femininity in Victorian literature. This research critically examines the dualistic portrayal of the protagonist, Tess, as both a "fallen angel" and a victim of rigid social constructs. Hardy’s narrative challenges traditional moral labels, blurring the lines between sin and virtue, agency and helplessness, personal choice and societal constraint. By positioning Tess in a world where patriarchal expectations and social hierarchies dictate the fate of women, Hardy highlights the systemic forces that shape her tragedy.This study explores how Tess’s character disrupts the archetypal image of the "fallen woman" common in 19th-century fiction, framing her not as a moral transgressor but as an emblem of innocence crushed by the hypocrisy and rigidity of Victorian social order. The research focuses on the symbolic and thematic elements that contribute to Tess’s portrayal — her connection to nature, her silence and voice at pivotal moments, and Hardy’s use of fate and fatalism. Furthermore, this paper investigates how the tension between purity and transgression reflects broader questions of gendered morality, victimhood, and societal judgment.Through a close reading of Hardy’s language, imagery, and narrative structure, the study reveals that Tess is constructed as both a subject of deep empathy and a cultural symbol of womanhood under siege. Hardy’s nuanced approach underscores the inadequacy of the simplistic labels society imposes on women, especially those marginalized by class and circumstance. Ultimately, this research aims to illuminate how Tess of the D’Urbervilles critiques Victorian gender ideologies, and how Hardy’s depiction of Tess encourages readers to question the myths of purity, morality, and female identity that persist even beyond his time.